Experimental and theoretical analysis on chamber pressure of a self-resonating cavitation waterjet. (1st March 2018) - Liu, Wenchuan; Kang, Yong; Zhang, Mingxing; Wang, Xiaochuan; Li, Deng; Xie, Lu
Abstract: Self-resonating cavitation waterjets (SRCW) offer the advantages of both cavitation jets and pulsed jets, and thus have been used in a broad array of practical and industrial applications. Pressure oscillations in the SRCW chamber are closely related to the resonating mechanism and the cavitation inception, and experiments focusing on the chamber pressure were conducted under various pressure drops and inspiratory methods. Hilbert-Huang transform (HHT) combined with empirical mode decomposition (EMD) were able to filter the undesired signals and provide a better frequency definition. Based on the experimental results, the bubble cluster accounts for the energy fluctuation and should be considered in frequency prediction. A modified model was proposed based on the combination of fluidic networks and the Gas-Spring Theory and in accordance with the frequency variation under various pressure drops. When air was introduced, the frequency characteristics is attributed to the unsteady motion of the mixture flow, in which the water and the bubble cluster appeared alternately. Highlights: A frequency model was proposed based on the combination of fluidic networks and the theory gas-spring. Hilbert-Huang transform (HHT) was adopted in filtering and analyzing the pressure signals in the chamber. The energy fluctuation of the bubble cluster was investigated. The modified model was in accordance in the frequency variations in experimental results. The frequency characteristics is due to the unsteady motion, in which the water and the bubble cluster appeared alternately.